2016
DOI: 10.1038/srep31430
|View full text |Cite
|
Sign up to set email alerts
|

Combined neonicotinoid pesticide and parasite stress alter honeybee queens’ physiology and survival

Abstract: Honeybee colony survival strongly relies on the queen to overcome worker losses exposed to combined stressors like pesticides and parasites. Queen’s capacity to withstand these stressors is however very little known. The effects of the common neonicotinoid pesticide imidacloprid in a chronic and sublethal exposure together with the wide distributed parasite Nosema ceranae have therefore been investigated on queen’s physiology and survivorship in laboratory and field conditions. Early physiological changes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 35 publications
0
46
0
2
Order By: Relevance
“…Коли швидкість утворення АФО переважає над швидкістю їх детоксикації, відбувається пошко-дження клітинних структур. За вираженого або тривалого стресу концентрація АФО у клітині може підвищуватися і тоді мобілізація захис-них систем клітини слабшає, у результаті чого активуються процеси, які спричиняють апоптоз або некроз [2,6,8,9,33]. Зумовити розвиток оксидативного стресу в організмі медоносної бджоли можуть вищезгадані чинники.…”
Section: Abstract: Bees Colony Collapse Syndrome Immunity Antioxidunclassified
“…Коли швидкість утворення АФО переважає над швидкістю їх детоксикації, відбувається пошко-дження клітинних структур. За вираженого або тривалого стресу концентрація АФО у клітині може підвищуватися і тоді мобілізація захис-них систем клітини слабшає, у результаті чого активуються процеси, які спричиняють апоптоз або некроз [2,6,8,9,33]. Зумовити розвиток оксидативного стресу в організмі медоносної бджоли можуть вищезгадані чинники.…”
Section: Abstract: Bees Colony Collapse Syndrome Immunity Antioxidunclassified
“…Studies have found that neonicotinoids have detrimental effects on bee navigation, motivation to forage, and social communication . They additionally negatively affect bee immunocompetence, gland and respiratory system development, reduce the survival of queens with Nosema infection, and reduce sperm viability in queens (Hatjina et al 2013, Chaimanee et al 2016, Dussaubat et al 2016). The fungicide chlorothalonil has been shown to alter the compilation of bee gut flora, potentially altering functionality resulting in decreased vigor (Kakumanu et al 2016).…”
Section: Varroa Destructor (Anderson and Trueman) Mite (Mullin Et Almentioning
confidence: 99%
“…Adult bee exposure to imidacloprid, during the first two weeks after emergence, negatively affects development of the hypopharyngeal glands and respiratory system (Hatjina et al 2013). Imidacloprid has also been shown to decrease the survival of queen honey bees that have Nosema ceranae infections (Dussaubat et al 2016). …”
Section: Pesticide Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it should be mentioned that Nicodemo et al (2014) showed that fipronil and imidacloprid impair energy production in mitochondria. Dussaubat et al (2016) studied sublethal effects of imidacloprid together with the widely distributed microsporidian parasite Nosema ceranae on queen's physiology and survivorship, both under laboratory and field conditions. The study showed that combined neonicotinoid pesticide and parasite stress alter honeybee queens' physiology and survival.…”
Section: Interactions With Other Stressorsmentioning
confidence: 99%